COMMUNITY WELFARE AND POVERTY IN REGENCIES/CITIES OF BALI PROVINCE FROM THE PERSPECTIVE OF THE CAPABILITY APPROACH - Ni Putu Reza Yunita Putri; I Gusti Agung Ayu Apsari Anandari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the factors influencing community welfare and poverty at the regency/city level in Bali Province using the Capability Approach perspective. The Capability Approach, developed by Amartya Sen, views welfare not only in terms of economic aspects but also through individuals’ capabilities in accessing education, health, and economic opportunities. This research employs secondary panel data from all regencies/cities in Bali during the 2020–2024 period, with key variables including access to education, unemployment rate, minimum wage, and access to healthcare. Data analysis is conducted using panel data regression to examine the effects of these variables on poverty and community welfare, measured through average per capita expenditure and the percentage of the poor population. The findings reveal that improved access to education and healthcare significantly reduces poverty levels and enhances community welfare. Conversely, unemployment has a positive effect on poverty, indicating that higher unemployment rates increase the number of poor people. The minimum wage is also found to play an important role in improving welfare and reducing poverty, although its effect is relatively smaller compared to education and healthcare access. The implications of this research suggest that local governments need to improve equitable access and quality of education and healthcare across regions, accompanied by policies that promote job creation and fair minimum wage setting.